PENYALAHGUNAAN IZIN TINGGAL KUNJUNGAN OLEH WARGA NEGARA ASING DALAM PERSPEKTIF HUKUM KEIMIGRASIAN INDONESIA - Rudianto; Devina Yuka Utami; Maidah Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the misuse of visit stay permits by foreign nationals from the perspective of Indonesian immigration law, focusing on a case involving 17 Vietnamese nationals working at a cosmetic surgery clinic. Occurring between 2018 and 2025, this case drew significant attention due to the violation of immigration regulations, as the individuals were engaged in activities that did not align with the purpose of their permitted stay. The aim of this research is to analyze how immigration law enforcement was applied in this case and to formulate preventive legal measures to avoid similar violations in the future. The research adopts a normative-empirical method with a qualitative approach. Data was collected through legal literature, academic journals, and other supporting documents, which were then analyzed normatively. This study emphasizes the importance of legal substance and institutional structure in the imposition of administrative sanctions for immigration violations. The case of the 17 Vietnamese nationals serves as a critical reference point in evaluating the effectiveness and fairness of immigration law enforcement on the ground. The findings reveal that the effectiveness of administrative sanctions in cases of permit misuse is influenced by five key factors: the clarity of applicable laws, the competence of law enforcement officials, the availability of supporting infrastructure, and public participation. Therefore, it is essential to implement sanctions that are not only legally appropriate but also capable of delivering a strong deterrent effect. The recommendations from this study are expected to contribute to the development of more responsive immigration policies and better prevention of future violations.